You Might Want to Engage Your Customers, But Choose Them Wisely: The Mixed Effects of Company-Initiated Customer Engagement on Customer Loyalty - Eggert, A.; Steinhoff, Lena; Witte, C. (2015 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)

The Interaction of Signals: A Fuzzy set Analysis of the Video Game Industry - Kaimann, Daniel; Cox, Joe
Customers continuously evaluate the credibility and reliability of a range of signals both separately and jointly. However, existing econometric studies pay insufficient attention to the interactions and complex combinations of these signals, and are typically limited as a result of difficulties controlling for multicollinearity and endogeneity in their data. We develop a novel theoretical approach to address these issues and study different signaling effects (i.e., word-of-mouth, brand reputation, and distribution strategy) on customer perceptions. Using data on the US video games market, we apply a fuzzy set qualitative comparative analysis (fsQCA) to account for cause-effect relationships. The results of our study address a number of key issues in the economics and management literature. First, our results support the contention that reviews from professional critics act as a signal of product quality and therefore positively influence unit sales, as do the discriminatory effects of prices and restricted age ratings. Second, we find evidence to support the use of brand extension strategies as marketing tools that create spillover effects and support the launch of new products.

The Economics of Individual Behavior in Competitive Environments: Empirical Evidence from Real-Life Tournaments - Scheel, Friedrich

Customer collectives in healthcare: The transformative potential of service to overcome consumer vulnerability - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 39th Annual Macromarketing Conference)

Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Stock Market Reactions to Customer Service Outsourcing in Manufacturing Firms - Eggert, A; Böhm, E; Cramer, C (2015 AMA Winter Marketing Educators’ Conference Proceedings)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V; Münkhoff, E; Scheer, L. K (ISBM 2014 Academic Conference)

Selling value in business markets: Why a powerful idea often fails - Eggert, A; Haas, A; Terho, H; Ulaga, W; Münkhoff, E (ISBM 2014 Academic Conference)

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 43rd European Marketing Academy (EMAC) Conference)

Overcoming Roadblocks to Value-Based Selling: Aligning Organizational Support With Sales Force Activities - Terho, H; Eggert, A; Ulaga, W; Haas, A (2014 AMA Winter Marketing Educators’ Proceedings)

Spillover Effects of Service Failures in Coalition Loyalty Programs: The Buffering Effect of Special Treatment Benefits. - Schumann, Jan H; Wünderlich, Nancy; Evanschitzky, Heiner (Journal of Retailing)
Coalition loyalty programs are on the rise, yet few studies investigate the impact of service failures in such programs. Using data from a retail context, the authors show that a program partner deemed responsible for a service failure suffers negative customer responses. However, customers’ perceptions of the benefits of the coalition loyalty program buffer these consequences. Perhaps most importantly, when customers perceive the program's special treatment benefits as low, direct and indirect spillover effects occur, such that a service failure by one program partner has a negative effect on customer loyalty toward the program itself.
Keywords: Service failure; Spillover effects; Buffering effect; Coalition loyalty program

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.

Revenue and profit implications of industrial service strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Muenkhoff, Eva (Journal of Service Research)

"Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change" - Djawadi, Behnud Mir; Fahr, Rene; Turk, Florian (Value in Health)

The Wage Effects of Social Norms-Evidence of Deviations from Peers' Body Mass in Europe - Janssen, Elmar; Fahr, Rene

The internal market and the consumer: what consumers actually choose - Thommes, Kirsten; Faure, Michael; Heine, Klaus (Colum. J. Eur. L.)

The dark side of solidarity: social norms and social relations in the aftermath of strikes - Thommes, Kirsten; Akkerman, Agnes; Torenvlied, René; Born, Marieke (Industrial relations journal)

Embracing complex causality with the QCA method: An invitation - Schneider, M; Eggert, A (Journal of Business Market Management)

Differential effects of product and service innovations on the financial performance of industrial firms - Eggert, A; Thiesbrummel, C; Deutscher, C (Journal of Business Market Management)

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus – Eine theoretische und empirisch-experimentelle Analyse

Gender and ethnic discrimination in hiring : evidence from field experiments in the German labor market - Kolle, Andre
The present thesis investigates the prevalence of and the reasons for hiring discrimination against women and ethnic Turks in the German labor market. Subsequent to a discussion of how to reveal discrimination, the literature on wage and employment differences inside and outside the German labor market is reviewed. Afterwards, different (economic) theories explaining inequalities in labor markets are presented. In the empirical analyses a field experiment - the so called correspondence testing - is conducted where matched pairs of (fictitious) male and female as well as German-named and Turkish-named applicants respond to, respectively, 656 and 608 (real) apprenticeship offers in predominantly male-dominated jobs. Descriptive results and econometric analyses using probit regressions on various model specifications indicate that the female applicant has a 19 percent lower callback probability compared to her male counterpart. However, differential treatment is both job- and firm-type driven. While callback rates are not statistically different from zero in female-dominated and “gender-neutral” occupations, they prevail in jobs where men are overrepresented. Furthermore, discrimination is restricted to late recruiters, i.e., companies that advertise their vacancies right before the apprenticeship is supposed to start. Similar conclusions can be drawn from the study investigating ethnic discrimination. The 32 percent lower callback probability of the Turkish-named applicant decreases if early rather than late recruiters are addressed. Apart from that, comparing response and callback rates to the candidates using different experimental designs, i.e., sending out single versus pairs of applications, yields no statistically significant differences demonstrating the unbiasedness of the correspondence approach.

Decision Making under Asymmetric Information in Markets for Experience Goods: Empirical Evidence of Signaling Effects on Consumer Perceptions - Kaimann, Daniel

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren

Vom Wollen und Können ethischen Entscheidens - Fahr, Rene (Theologie und Glaube)

Verantwortungsvolles Handeln in Unternehmen. Die Rolle von kognitiven Verzerrungen und Selbsttäuschung bei ethischen Entscheidungen - Fahr, Rene

Contagious conflict: spill-over effects of labor conflict between and within organizations - Akkerman, Agnes; Torenvlied, René; Lehr, Alex; Thommes, Kirsten (Social conflict within and between groups)

Die Rechte von Arbeitnehmervertretern in Ost- und Westeuropa - Einheitseuropa oder Zweiklassengesellschaft? - Thommes, Kirsten; Walgenbach, Peter; Oertel, Simon

The Role of prior Entrepreneurial Exposure in the Entrepreneurial Process: A Review and Future Research Implications. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management.)

Social media and e-participation: Challenges of social media for managing public projects. - Vogt, S; Förster, B; Kabst, Rüdiger (International Journal of Public Administration in the Digital Age.)

Foreign Direct Investments and domestic employment of German SMEs: The moderating effect of owner-management. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management (JSBM).)

Linking Transaction Cost and Social Exchange Theory to Explain Strategic Alliance Performance: A Meta-Analytic Structural Equation Model. - Isidor, R; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger (International Journal of Strategic Business Alliances.)

Configurations of e-HRM - An Empirical Exploration. - Strohmeier, S; Kabst, Rüdiger (Employee Relations.)

Playing hard to get: an economic rationale for crowding out of intrinsically motivated behavior - Schnedler, Wendelin; Vanberg, Christoph (European Economic Review)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (43rd EMAC Annual Conference, Valencia)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V.; Münkhoff, Eva; Scheer, L. K. (ISBM 2014 Academic Conference, San Francisco, CA)

Salespersons’ solution crafting capability: A knowledge-based perspective - Münkhoff, Eva; Eggert, A.; Terho, H.; Haas, A.; Ulaga, W. (ISBM 2014 Academic Conference, San Francisco, CA)

Selling value in business markets: Why a powerful idea often fails - Eggert, A.; Haas, A.; Terho, H.; Ulaga, W.; Münkhoff, Eva (ISBM 2014 Academic Conference, San Francisco, CA)

Revenue and Profit Implications of Industrial Service Strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Münkhoff, Eva (Journal of Service Research)
In many business markets, manufacturers seek service-led growth to secure their existing positions and continue to grow in increasingly competitive environments. Using longitudinal data from 513 German mechanical engineering companies and latent growth curve modeling, this study offers a fine-grained view of the financial performance implications of industrial service strategies. By disentangling the revenue and profit implications of industrial service strategies, findings reveal that such strategies increase both the level and the growth of manufacturing firms’ revenue streams. In contrast, they reduce the level but improve the growth of manufacturers’ profits. Results further suggest that services supporting the clients’ actions (SSC) and services supporting the supplier’s product (SSP) affect performance outcomes in different ways. SSCs directly affect revenue and profit streams. In turn, SSPs display only indirect effects on financial performance mediated through SSCs. A moderator analysis identifies two organizational contingencies that facilitate service business success: Only companies with decentralized decision-making processes and a high share of loyal customers can expect favorable financial results from industrial service strategies. In summary, this research provides significant insights and managerial guidance for turning service strategies into financial successes.
Keywords: Organizational Behavior and Human Resource Management; Sociology and Political Science; Information Systems

Embracing complex causality with the QCA method: An invitation - Schneider, Martin; Eggert, Andreas (Journal of Business Market Management)

A matter of degree: the continuing training gap for women in Europe - Wozny, Caroline; Schneider, Martin (Socio-Economic Review)

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus – Eine theoretische und empirisch-experimentelle Analyse - Steinhoff, Lena

How Profound Is the Allure of Endowed Status in Hierarchical Loyalty Programs? - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Three Perspectives for Making Loyalty Programs More Effective - Steinhoff, Lena; Palmatier, R. W. (Customer & Service Systems, Special Issue: Customer Empowerment, 1 (1))

Consequences of Customer Engagement: How Customer Engagement Alters the Effects of Habit-, Dependence-, and Relationship-Based Intrinsic Loyalty, Marketing Science Institute (MSI) Working Paper Series. - Henderson, C. M.; Steinhoff, Lena; Palmatier, R. W.

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Annual Meeting Proceedings)

Can service innovations substitute or complement product innovations? The case of German industrial firms - Eggert, A; Thiesbrummel, C; Deutscher, C (Proceedings of the 20th International Product Development Management Conference)

Increasing Customers' Willingness to Pay for Hybrid Offerings: The Impact of Price Presentation Formats - Eggert, A; Ulaga, W; Steiner, M; Backhaus, K (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

Threat and normative appeals to reduce product returns in online retailing – An effective marketing practice? - Garnefeld, I; Münkhoff, E; Raum, K (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

How to prolong a sales promotion – Ex-post time extension versus reframing - Münkhoff, E; Garnefeld, I; Bruns, A (roceedings of the 42nd European Marketing Academy (EMAC) Conference)

Creating Emotional Brand Attachment through the Salesperson's Brand-Consistent Behavior - Posner , T; Garnefeld, I; Eggert, A (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

The Effect of Loyalty Programs on Target and Bystander Customers: A Customer Portfolio Perspective on Loyalty Program Performance - Steinhoff, L; Palmatier, R. W (Proceedings of the 42nd European Marketing Academy (EMAC) Conference)

Exploring differential effects of product and service innovations on industrial firms’ financial performance - Eggert, A; Thiesbrummel, C; Deutscher, C (2013 AMA Winter Marketing Educators' Proceedings)

High Tech and High Touch: A Framework for Understanding User Attitudes and Behaviors Related to Smart Interactive Services. - Wünderlich, Nancy; Wangenheim, Florian V; Bitner, Mary Jo (Journal of Service Research)
Smart interactive services, in contrast with other technology-based services, require significant human-to-human interaction and collaboration in addition to the service provided by the embedded technology itself. The authors’ foundational Delphi study confirms smart interactive services (e.g., remote diagnosis, remote repair of equipment, and telemedicine) are a rapidly growing innovation category across industries. Yet, gaining user acceptance of these types of services presents a significant challenge for managers. To address this challenge, the authors employ a grounded theory approach, drawing on depth interviews, to develop a framework of barriers and facilitators to users’ attitudinal and behavioral responses to smart interactive services. The findings reveal a new set of beliefs that are critical in this context. These beliefs are tied to the human element and specifically pertain to beliefs about the “service counterpart (SC),” who is the provider’s employee controlling the technology. Control, trustworthiness, and collaboration beliefs emerge jointly as important and interrelated influencers tied to the SC. Contrary to conventional wisdom that focuses on features of the technology itself to gain user acceptance, this research encourages providers to emphasize the interpersonal elements of the service by providing control cues, raising social presence, and enhancing human trust mechanisms.
Keywords: service technology; technology-mediated service; service counterpart; smart service; remote service; technology adoption

Editorial: Internationales Personalmanagement: Den kulturellen Kontext gestalten - Kabst, Rüdiger; Wehner, M C (PERSONALquartely)

Unterstützung von Kommunalverwaltung bei Bürgerbeteiligung - Weber, P; Kabst, Rüdiger (Verwaltungskommunikation - Wissenschaftliche Analyse und praktische Beispiele)

Institutional Determinants of Work-Family Practices: An International Comparative Examination. - Weber, H; Wehner, M; Kabst, Rüdiger

HR-Praktiken und Innovation: Wie können Wissens- und Technologievorsprünge im Unternehmen generiert werden? - Golubovic, S; Wehner, M; Baum, M; Kabst, Rüdiger

Institutional Pressures and Interorganizational Imitation: A Quasilongitudinal Analyses of Temporary Work in the UK and Germany - Isidor, R; Wehner, M; Li, C; Kabst, Rüdiger

The Impact of Individual and Collective Reputation on Wine Prices: Empirical Evidence from the Mosel Valley - Frick, Bernd; Simmons, Robert (Journal of Business Economics)
Although of considerable practical importance, the separate impact of individual and collective reputation on firm performance (e.g. product prices) has not yet been convincingly demonstrated. We use a sample of some 70 different wineries offering more than 1,300 different Riesling wines from the Mosel valley to isolate the returns to individual reputation (measured by expert ratings in a highly respected wine guide) from the returns to collective reputation (measured by membership in two different professional associations where members are assumed to monitor each other very closely). We find that both effects are statistically significant and economically relevant with the latter being more important in quantitative terms than the former.

Growing existing customers' revenue streams through customer referral programs - Garnefeld, Ina; Eggert, Andreas; Helm, Sabrina V; Tax, Stephen S (Journal of Marketing)

Erfolgsfaktor Value-Based Selling—Verkaufen, wenn Kundenorientierung nicht zum Erfolg führt - Haas, Alexander; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang (Marketing Review St. Gallen)

Individual determinants of work attendance: Evidence on the role of personality - St{\, Susi; Fahr, Rene (Applied Economics)

Arbeitskräftebedarf bei hoher Arbeitslosigkeit: ein ökonomisches Zuwanderungskonzept für Deutschland - Zimmermann, Klaus F; Bauer, Thomas K; Bonin, Holger; Fahr, Rene; Hinte, Holger

The impact of risk perception and risk attitudes on corrupt behavior: Evidence from a petty corruption experiment - Mir Djawadi, Behnud; Fahr, Rene

Born in the GDR: Imprinting, Structural Inertia and the Survival Chances of Organizations - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter (Academy of Management Proceedings)

The after effects of strikes on team collaboration-experimental evidence - Thommes, Kirsten; Akkerman, Agnes; Vyrastekova, Jana (Academy of Management Proceedings)

Primacy versus Recency Effects in Extended Service Encounters - Garnefeld, Ina; Steinhoff, Lena (Journal of Service Management)

Umsatz- und Profitabilitätsauswirkungen industrieller Dienstleistungen – Eine latente Wachstumskurvenanalyse

„Sekretärin des Vorstandes“ gesucht: Stellenanzeigen und die expressive Funktion des AGG - Bauhoff, Frauke; Schneider, Martin (Industrielle Beziehungen/The German Journal of Industrial Relations)

International as Opposed to Domestic New Venturing: The Moderating Role of Perceived Barriers to Internationalization. - Baum, M; Schwens, C; Kabst, Rüdiger (International Small Business Journal (ISBJ).)

Conjoint implications on job preferences: The moderating role of involvement. - Baum, M; Kabst, Rüdiger (International Journal of Human Resource Management (IJHRM).)

How to attract applicants in the atlantic versus the asia-pacific region? A cross-national analysis on China, India, Germany, and Hungary. - Baum, M; Kabst, Rüdiger (Journal of World Business (JWB).)

Gender Effects on Entrepreneurial Intention: A Meta-Analytical Structural Equation Model. - Haus, I; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger (International Journal of Gender and Entrepreneurship (IJGE))

Analyzing observed composite differences across groups: Is partial measurement invariance enough? - Steinmetz, Holger (European Journal of Research Methods for the Behavioral and Social Sciences.)

Threat and normative appeals to reduce product returns in online retailing – An effective marketing practice? - Garnefeld, I.; Münkhoff, Eva; Raum, K. (42nd EMAC Annual Conference, Istanbul)

How to prolong a sales promotion – Ex-post time extension versus reframing - Münkhoff, Eva; Garnefeld, I.; Bruns, A. (42nd EMAC Annual Conference, Istanbul)

Umsatz- und Profitabilitätsauswirkungen industrieller Dienstleistungen - Münkhoff, Eva

"Gung Ho": Nationale Kultur und Schlanke Produktion in Ron Howards Spielfilm. - Schneider, Martin (Macht und Employment Relations)

Primacy versus Recency Effects in Extended Service Encounters - Garnefeld, I.; Steinhoff, Lena (Journal of Service Management)

The Effect of Loyalty Programs on Target and Bystander Customers: A Customer Portfolio Perspective on Loyalty Program Performance - Steinhoff, Lena; Palmatier, R. W. (Proceedings of the 42nd European Marketing Academy (EMAC) Conference, Istanbul)

Understanding the Effectiveness of Loyalty Programs, Marketing Science Institute (MSI) Working Paper Series - Steinhoff, Lena; Palmatier, R. W.

The Bright and Dark Side of Endowed Status in Hierarchical Loyalty Programs - Eggert, A; Garnefeld, I; Steinhoff, L (2012 AMA Summer Marketing Educators' Proceedings)

I thought it was all over and now it is back again – Customer reactions to time extensions of sales promotions - Garnefeld, I; Münkhoff, E; Bruns, A (2012 AMA Summer Marketing Educators’ Proceedings)

Capturing the Value of Hybrid Offerings: The Impact of the Price Presentation Format - Eggert, A; Steiner, M; Ulaga, W; Backhaus, K (Proceedings of the 2012 ISBM Academic Workshop)

Dispersion of Market Activities: A Configurational Approach - Ritter, T; Eggert, A (Proceedings of the 2012 ISBM Academic Workshop)

Growing with Industrial Services - A Configurational Approach - Eggert, A; Münkhoff, E; Thiesbrummel, C (2012 AMA Winter Marketing Educators' Proceedings)

Endowed Status in Hierarchical Loyalty Programs - Eggert, A; Garnefeld, I; Steinhoff, L (2012 AMA Winter Marketing Educators' Proceedings)

Growing Existing Customers’ Profitability with Customer Referral Programs - Garnefeld, I; Helm, S; Eggert, A; Tax, S (2012 AMA Winter Marketing Educators' Proceedings)

Perils of Managing the Service Profit Chain: The Role of Time Lags and Feedback Loops. - Evanschitzky, Heiner; Wangenheim, Florian v; Wünderlich, Nancy (Journal of Retailing)
The tendency of managers to focus on short-term results rather than on sustained company success is of particular importance to retail marketing managers, because marketing activities involve expenditures which may only pay off in the longer term. To address the issue of myopic management, our study shows how the complexity of the service profit chain (SPC) can cause managers to make suboptimal decisions. Hence, our paper departs from past research by recognizing that understanding the temporal interplay between operational investments, employee satisfaction, customer satisfaction, and operating profit is essential to achieving sustained success. In particular, we intend to improve understanding of the functioning of the SPC with respect to time lags and feedback loops. Results of our large-scale longitudinal study set in a multi-outlet retail chain reveal time-lag effects between operational investments and employee satisfaction, as well as between customer satisfaction and performance. These findings, along with evidence of a negative interaction effect of employee satisfaction on the relationship between current performance and future investments, show the substantial risk of mismanaging the SPC. We identify specific situations in which the dynamic approach leads to superior marketing investment decisions, when compared to the conventional static view of the SCP. These insights provide valuable managerial guidance for effectively managing the SPC over time.
Keywords: Employee satisfaction; Customer satisfaction; Performance; Service profit chain; Feedback loops; Time lags; Myopic marketing management

Culture’s Impact on Customer Motivation to Engage in Professional Service Enactments. - Schumann, Jan H; Wünderlich, Nancy; Zimmer, Marcus S (Schmalenbach Business Review)
Although professional service providers increasingly deliver their services globally, little is known about cross-cultural differences in customers’ motivation to participate in service production. To address this lacuna, we survey a total of 2,284 banking customers in 11 countries on their motivation to provide personal information to, and follow the advice of, their service providers. We find differences in both aspects, but only the differences in providing personal information can be explained by the cultural values of uncertainty avoidance, individualism/collectivism, and masculinity/femininity. To perform certain tasks in the service process, global professional service providers should acknowledge cultural differences in customers’ motivations.
Keywords: Co-Production; Culture; Customer Participation; Professional Services

Technology Mediation in Service Delivery: A New Typology and an Agenda for Managers and Academics. - Schumann, Jan H; Wünderlich, Nancy; Wangenheim, Florian (Technovation)
The role of information and communication technology for economic growth has been emphasized repeatedly. Technological breakthroughs have generated new forms of services, such as self-services or remote services. Although these encounters are qualitatively different from traditional service provision, prior service management literature thus far had paid little attention to theory development and the systematization of technology-based service encounters. To fill this research gap, the present study outlines how new types of technology-based services fit into existing service typologies and provides an extension of existing frameworks to capture their unique characteristics. These insights in turn offer managerial implications and highlight open research questions.
Keywords: Services; Remote services; Self-services; Technology mediation

Das Cranet-Projekt: Kreuzkulturelle Vergleiche im HR-Management. - Steinmetz, Holger; Schwens, C; Wehner, M; Kabst, Rüdiger (PERSONALquartely)

Editorial: Employer Branding: Strategie, Instrumente, Umsetzung - Kabst, Rüdiger; Baum, M (PERSONALquartely)

Einführung in die Betriebswirtschaftslehre - Weber, W; Kabst, Rüdiger

Determinants of Different Types of Born Globals. - Baum, M; Schwens, C; Kabst, R (Handbook of Research on Born Globals)

Die Messung von Joint-Venture Erfolg - Isidor, R; Schwens, C; Kabst, R (Markteintrittsstrategien - Dynamik und Komplexität)

Diversität, Konflikte und Leistung in Teams: Ein meta-analytisches Strukturgleichungsmodell - Schneid, M; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger

Endogeneity in the behavioral sciences: An illustration with real data - Kabst, Rüdiger

Recruitment Process Outsourcing and Applicant Reactions: Does Image Make a Difference? - Wehner, M C; Giardini, A; Kabst, Rüdiger